Herding and Positive Feedback Trading in the Portuguese Stock Exchange: An Exploratory Investigation - Ferreira, Mario Pedro (2010)
The heterogeneity inherent in the composition of the investors’ population is a factor conducive to the complexity of the market. Heterogeneous backgrounds are expected to lead to divergence in investors’ decision-making. However, evidence suggests that the temporary convergence of beliefs and actions is a possibility. Our research attempts to address the issue of two aspects of this convergence, namely positive feedback trading (“trend-chasing”) and herding. Using data from the Portuguese PSI-20 market index, we test for herding and positive feedback trading for the period since the inception of the PSI-20 (January 1993). Results indicate the significance of herding and positive feedback trading towards the index, both of which appear to be experiencing a sharp rise between 1996 and 1999. This coincides with the Portuguese market’s “boom-bust” in the second half of the 1990’s. In line with Hwang and Salmon (2004), herding appears to be rising during periods of “definitive” market direction and exhibits descending tendencies during periods of market fluctuations.